2015
DOI: 10.1039/c5ra01011j
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of gaseous elemental mercury with activated carbon impregnated with ferric chloride

Abstract: Fe-based modified activated carbon prepared by impregnation was used for adsorbents in Hg 0 purification.The influence of carriers, active components, FeCl 3 solution concentration and calcination temperature, were investigated for Hg 0 adsorption purification. The effects of the preparation conditions on the adsorbent were characterized by N 2 adsorption-desorption isotherms, scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD) and (FTIR). The samples modified wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…It has been well-demonstrated that introduction of oxygen functionalities onto carbon materials is a promising strategy to enhance its adsorption capacity of heavy metal ions. [21][22][23][24] Aer activation in either gas or liquid phase with oxidants/reductants, the post-oxidation/reduction treatments of commercial activated carbon or carbon materials have been successfully applied to increase the surface oxygenated groups, eventually promoting adsorption ability. These modication techniques not only involve time-consuming and additional processes, but also lead to a drastic reduction of the total basic groups, such as the chemical treatments with H 2 O 2 , 25 HNO 3 , 26 (NH 4 ) 2 S 2 O 8 , 27 and O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been well-demonstrated that introduction of oxygen functionalities onto carbon materials is a promising strategy to enhance its adsorption capacity of heavy metal ions. [21][22][23][24] Aer activation in either gas or liquid phase with oxidants/reductants, the post-oxidation/reduction treatments of commercial activated carbon or carbon materials have been successfully applied to increase the surface oxygenated groups, eventually promoting adsorption ability. These modication techniques not only involve time-consuming and additional processes, but also lead to a drastic reduction of the total basic groups, such as the chemical treatments with H 2 O 2 , 25 HNO 3 , 26 (NH 4 ) 2 S 2 O 8 , 27 and O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…First, Hg 0 was absorbed on the AC surface to form Hg 0 (ad). Then, HgCl 2 generated through Hg 0 (ad) reacted with CCl group . The reactions are given as follows: Hnormalg0+ACHnormalg0true(normalanormaldtrue) Hnormalg0true(normalanormaldtrue)+CClHnormalgCl+C HnormalgCl+CClHgCnormall2+C …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a large amount of nanoparticles suspension leads to an increase in the blanks signal. The graphene shows similar properties to activated carbon so it can adsorb the gaseous species of mercury present in the air during the preparation of the nanoparticles suspension [38][39][40]. This could lead to the contamination in the blanks, making necessary to work under a clean atmosphere and to minimize the amount of nanoparticles suspension.…”
Section: Amount Of Nanoparticlesmentioning
confidence: 99%